New occurrences and habitat description of southern Ecuador endemic frog Atelopus exiguus (Anura: Bufonidae) from a conservation hotspot in the high Andes - Astudillo, Pedro X. (2022)
Atelopus species are classified as a priority taxon for monitoring and conservation, of these A. exiguus is endemic to southern Ecuador and is classified as critically endangered, however, within its known geographic range, little attention has been given to identifying new localities particularly across the páramo ecosystem (> 3500 m a.s.l.). Therefore, in the páramo landscape of Macizo del Cajas Biosphere Reserve, a conservation hotspot, we intensively searched for A. exiguus across 15 localities (elevation range: 3550 – 3800 m a.s.l.). In one year of monitoring (2020 – 2021), we recorded four individuals of A. exiguus (two were tadpoles) in two localities. The localities are characterized by a higher proportion of páramo grassland in association with shrubby páramo as well as cushion páramo; this riparian habitat is related to relatively good water quality (according to Andean Biotic Index), relatively low water temperatures and relatively low water flow. Our findings, accompanied by a detailed monitoring protocol, suggest habitat requirements for A. exiguus. Further intensive surveys beyond the limits of protected areas of Azuay province, especially across the páramos, is emerging as an urgent step to improve conservation decisions.